1963
DOI: 10.1021/jf60128a015
|View full text |Cite
|
Sign up to set email alerts
|

Protein Purification, Alcohol Washing of Soybean Protein

Abstract: Soybean protein isolated by acidification of an aqueous extract of hexane-defatted soybean meal contains 2 to 4% of a phospholipide-like material. These lipides cannot be removed by isoelectric precipitation, washing with water, dialysis, or ammonium sulfate precipitation. However, they are extractable with aqueous alcohols. The concentration of alcohol used to wash the protein has a pronounced effect on the amount of material removed and on the nitrogen content of the extracted protein. Optimum concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1969
1969
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…During the past decades, many researches have been carried out to improve the flavor, color and functionalities of the isolated protein. Among these, alcohol leaching has demonstrated high potential in improving the quality of soy protein product (Beckel & Smith, 1944;Baker, Mustakas, & Warner, 1979;Eldridge, Wolf, Nash, & Smith, 1963;Grant et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, many researches have been carried out to improve the flavor, color and functionalities of the isolated protein. Among these, alcohol leaching has demonstrated high potential in improving the quality of soy protein product (Beckel & Smith, 1944;Baker, Mustakas, & Warner, 1979;Eldridge, Wolf, Nash, & Smith, 1963;Grant et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Demonstration that measurable amounts of lipid material remain in protein isolated from hexane-extracted soybean flakes suggests that oxidation of lipid components may be a factor in the flavor of soybean protein products (7). Removal of much of the flavor and lipid material by extraction of dehulled, defatted soybean flakes with alcohols supports this suggestion (8).…”
Section: Identification Of Flavor Componentsmentioning
confidence: 97%
“…Earlier we mentioned some studies involving extraction with alcoholic solvents. Alcoholic treatment does partly inactivate enzymes in soybeans and does remove substantial amounts of hpids and flavor (5,7,8,20). Alcohol suffers from some of the same disadvantages as cooking and steaming.…”
Section: Procedures For Removing Flavormentioning
confidence: 99%
“…It has been shown that oleosin-PL complexes remain intact during SP extraction from soybean and are isolated along with purified SP [7]. Previously, removal of PLs from SP has been attempted using solvents like aqueous alcohols (78-97%, v/v) [8]; hexane/alcohol azeotropes [9,10]; methylene chloride, and aqueous acetone [11]. While these treatments proved very effective in reducing PL levels and concomitantly improving SP flavor, exposure to solvent resulted in severe protein denaturation and subsequent loss of solubility [9,10,12].…”
Section: Introductionmentioning
confidence: 99%